ANALISIS STATUS MUTU AIR SUNGAI KARANG MUMUS DAN DAMPAK KESEHATAN SEGMEN TANAH DATAR DAN WADUK BENANGA KOTA SAMARINDA - Anggita Yudha Septyawan; Vita Pramaningsih; Hansen Hansen (Universitas Lambung Mangkurat, 2022)
Water is an environmental component that has an important role in human life. Water is needed by humans in daily activities. Increasing population and environmental changes have an impact on water quality, one of which is river water. Polluted river water is very dangerous for public health. The purpose of this research is to determine the status of river water quality and also the health impact of the Tanah Datar and Benanga Reservoir segments related to the use of river water. The method to identify the health impact is an interview with a questionnaire. Determination of quality status using the pollution index method with parameters TSS, pH, BOD, COD, DO, nitrate, phosphate and fecal coli. The study showed that in the Flatland segment, the COD and pH parameters did not meet, while in the Benanga fecal coli reservoir segment, the parameters did not meet the quality standards. The river water pollution index for the Tanah Datar segment is 0.8818 and the Benanga Reservoir segment is 2.5442. The study showed that there were 6 respondents from Tanah Datar and 9 respondents from Benanga Reservoir who experienced skin irritation. The results showed that the water quality status of the Tanah Datar segment was in good condition, while the river water of the Benanga Reservoir segment was in a light polluted condition. High COD parameters in Tanah Datar caused skin irritation to respondents, high fecal coli in Benanga Reservoir did not cause skin irritation to respondents.